Modern Concepts in Cardiovascular Disease: Inflamm-Aging - Puspitasari, Yustina M.; Ministrini, Stefano; Schwarz, Lena; Karch, Caroline; Liberale, Luca; Camici, Giovanni G. (Frontiers in Cell and Developmental Biology, 2022)
The improvements in healthcare services and quality of life result in a longer life expectancy and a higher number of aged individuals, who are inevitably affected by age-associated cardiovascular (CV) diseases. This challenging demographic shift calls for a greater effort to unravel the molecular mechanisms underlying age-related CV diseases to identify new therapeutic targets to cope with the ongoing aging "pandemic". Essential for protection against external pathogens and intrinsic degenerative processes, the inflammatory response becomes dysregulated with aging, leading to a persistent state of low-grade inflammation known as inflamm-aging. Of interest, inflammation has been recently recognized as a key factor in the pathogenesis of CV diseases, suggesting inflamm-aging as a possible driver of age-related CV afflictions and a plausible therapeutic target in this context. This review discusses the molecular pathways underlying inflamm-aging and their involvement in CV disease. Moreover, the potential of several anti-inflammatory approaches in this context is also reviewed.